Modelling and simulation of industrial trickle bed reactor hydrotreating for whole fraction low-temperature coal tar simultaneous hydrodesulfurisation and hydrodenitrification. (1st June 2020) - Fan, Xiaoyong; Li, Dong; Feng, Xian; Dong, Huan; Liu, Xu; Dan, Yong; Zheng, Huaan; Fan, An; Li, Wenhong
Highlights: Three quench-four beds whole fraction LTCT industry TBR model simultaneous HDS and HDN was constructed. A bed configuration with equal bed lengths and unequal bed inlet temperature was established for the high exothermic characteristics. The method for establishing the whole fraction LTCT TBR model can provide new ideas for the scale-up and design of industrial reactors. Abstract: Whole fraction low-temperature coal tar (LTCT) has a high content of heavy compounds, direct entry into an industrial reactor for hydrotreating (HDT) conversion into fuel oil is a new technology that has not been widely reported. Furthermore, a copious amount of heat is generated, resulting in hot spots and temperature flying on the catalyst bed. This study uses the gPROMS software, based on the kinetic parameters which are determined from several HDT reactions using experimental data in small-scale TBR, combined with energy balance and mass transfer equations among three phases to construct industrial TBR model with a treatment capacity of 250, 000 tons/year. This model was used for simultaneous HDS and HDN process simulation. The Simulation results show that the sharp temperature rise along the catalyst bed length can arrive at 70 K without quenching, which is obviously higher than that of petroleum distillate hydrogenation. So, a optimal bed configuration of equal bed lengths and unequal bed inlet temperature was established by simulating and optimizing the reactor. with each bed 350 cm in length and inlet temperatures of 633 K, 643 K, 653 K, and 653 K, respectively, it has a reasonable temperature rise distribution, lower added hydrogen quench amount of 47360.65 Nm 3 /h, while sulfur and nitrogen removal rates can reach 87.55% and 86.46%, showing better performance than that of a small scale reactor. Hydrogen quenching not only lowers the temperature of the mixture and replenishes the chemical hydrogen consumption but also facilitates the removal of S, N heteroatom compounds. The results can provide a guidance for bed configuration for whole fraction LTCT industrial hydrogenation devices.